2010
DOI: 10.3168/jds.2010-3054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different rumen-inert fatty acids supplemented with a dietary antioxidant on performance and antioxidative status of early-lactation cows

Abstract: The objective of the study was to evaluate the effect of diets supplemented with fatty acids of different degrees of saturation, in the absence or presence of an antioxidant (AOX; Agrado Plus, Novus International Inc., St. Charles, MO), on dairy cow lactation performance. Calcium salts of long-chain fatty acids were supplemented as a source of lower saturation fatty acid, and a palm acid product was supplemented as the higher saturation fatty acid source. Sixty early-lactation Chinese Holstein cows (100+/-23 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 30 publications
(38 reference statements)
4
28
1
2
Order By: Relevance
“…A future study should examine what products of n-3 FA metabolism may affect the oxidant balance after a one-time dose in colostrum as reported in the current study. Our observation of decreased RONS production by the n-3 FA in FFE may have further improved with the addition of 200 mg (334 IU) of α-tocopherol, which was included to protect n-3 FA from peroxidation (Wang et al, 2010). In our study, we observed decreased α-tocopherol concentrations in FFE calves during wk 1.…”
Section: Discussionsupporting
confidence: 59%
“…A future study should examine what products of n-3 FA metabolism may affect the oxidant balance after a one-time dose in colostrum as reported in the current study. Our observation of decreased RONS production by the n-3 FA in FFE may have further improved with the addition of 200 mg (334 IU) of α-tocopherol, which was included to protect n-3 FA from peroxidation (Wang et al, 2010). In our study, we observed decreased α-tocopherol concentrations in FFE calves during wk 1.…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, Jacobs et al (2013) observed that C18:2cis-9,cis-12 and C18:3cis-9,cis-12,cis-15 FA reduced mRNA abundance of acetylcoenzyme A (CoA) carboxylase (ACACA), fatty acid synthase (FASN; trend at P ¼0.07) and stearoyl-CoA 1 (SCD1), as well as the transcription factor sterol regulatory element binding factor (SREBP1) in bovine mammary epithelial cells. Other studies also have suggested that polyunsaturated FA increase free radical load in ruminants (Vázquez-Añón and Jenkins, 2007;Vazquez-Anon et al, 2008;Wang et al, 2010) as shown by higher lipoperoxidation susceptibility of plasma in sheep (Gladine et al, 2007) and dairy cows (Gobert et al, 2009) supplemented with omega-3-rich diets. Although the physiological basis for this response to lipid supplements is not totally understood yet, failure of the endogenous antioxidant system in preventing lipoperoxidation may be involved as shown by reduced activity of GPX in plasma of dairy cows infused with FO (Côrtes et al, 2012).…”
Section: Introductionmentioning
confidence: 94%
“…During the transition dairy cow undergo a period of negative energy balance for the demands of milk synthesis, which cannot be met by feed intake (Wang et al, 2010). Ketosis, one of the most prevalent metabolic diseases in dairy cows during transition period, was a condition that the concentration of ketone in blood was exceeding than 3,000mol/L (Oetzel, 2007) during the transition (Shire et al, 2013;Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%